2022
DOI: 10.3389/fgene.2022.968376
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the model for predicting prognosis by key genes regulating EGFR-TKI resistance

Abstract: Background: Previous studies have suggested that patients with lung adenocarcinoma (LUAD) will significantly benefit from epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI). However, many LUAD patients will develop resistance to EGFR-TKI. Thus, our study aims to develop models to predict EGFR-TKI resistance and the LUAD prognosis.Methods: Two Gene Expression Omnibus (GEO) datasets (GSE31625 and GSE34228) were used as the discovery datasets to find the common differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Some of the GT genes identified in this study have previously been shown to have important functions in malignancies, including LUAD. Prior research has linked elevated FUT1 expression to a favorable EGFR-TKI response [ 11 ]. In our study, LUAD patients with high FUT1 expression exhibited a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the GT genes identified in this study have previously been shown to have important functions in malignancies, including LUAD. Prior research has linked elevated FUT1 expression to a favorable EGFR-TKI response [ 11 ]. In our study, LUAD patients with high FUT1 expression exhibited a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Its downregulation may contribute to enhanced tumor cell invasiveness and metastasis. Studies exploring the clinical relevance of CCDC80 in ovarian cancer patients are underway; they aim to elucidate its impact on disease progression and patient survival [59].…”
Section: Prognostic Genesmentioning
confidence: 99%
“…Gene expression analysis has revealed that the mRNA expression of FUT2, FUT3, FUT6, and FUT8 are increased in NSCLC, whereas that of FUT1 is decreased ( 112 ). FUT1 expression has been correlated with treatment outcomes in LUAD patients receiving epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) ( 73 ). FUT2 is overexpressed in LUAD and may facilitate autophagy and suppress apoptosis via the p53 and JNK pathways ( 74 ), as well as induce EMT through TGF-β/Smad signaling in LUAD ( 75 ).…”
Section: Glycoenzyme-based Protein Glycosylation Changes In Crdsmentioning
confidence: 99%